Applying the intervention programme in clinical practice - Hajduchová, Hana; Brabcová, Iva; Tóthová, Valérie; Bártlová, Sylva; Doseděl, Martin; Malý, Josef; Vlček, Jiří (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2019)
The goal is to present partial results of the programme which was carried out in order to decrease the incidence of falls of hospitalized patients. Materials and methods: In January 2018, 16 monitored departments in 4 South Bohemian hospitals started the annual intervention programme, the goal of which was to reduce the incidence of falls. The selected (intervention) nurses were responsible for the realization and coordination of the interventions of fall prevention in co-operation with the managers of selected departments. The interventions included the identification of fall risk patients and standard nursing interventions in fall risk patients (by the departments’ standards) as well as the trainings of nurses in fall prevention of hospitalized patients, individual education of patients and their close relatives, special labelling of the beds of fall risk patients, and ensuring compensation and safety aids and after-fall medical audit using interactive databases.This article presents the data from only two selected departments (internal department and subsequent care department of the South Bohemian regional hospital), which recorded a decrease of falls compared to the same period in 2017. The internal department recorded 27 falls in 2018 (in 2017, there were 42 falls) and the subsequent care department recorded 18 falls in 2018 (in 2017, there were 38 falls). This article presents the data from only two selected departments (internal department and subsequent care department of the South Bohemian regional hospital), which recorded a decrease of falls compared to the same period in 2017. The internal department recorded 27 falls in 2018 (in 2017, there were 42 falls) and the subsequent care department recorded 18 falls in 2018 (in 2017, there were 38 falls). Conclusion: Despite all measures, we recorded falls of patients in the monitored period (January–December 2018). However, it is positive that most workplaces included in our programme recorded a decrease compared to last year.
Aplikace intervenčního programu do klinické praxe
Keywords: Hospitalized patients; Intervention programme; South Bohemian hospitals; Prevention of falls; hospitalizovaní pacienti; intervenční program; jihočeské nemocnice; prevence pádů